2002
DOI: 10.1136/bmj.324.7336.524
|View full text |Cite
|
Sign up to set email alerts
|

A comparative case study of two models of a clinical informaticist service

Abstract: Objectives To describe and evaluate two different models of a clinical informaticist service. Design A case study approach, using various qualitative methods to illuminate the complexity of the project groups' experiences. Setting UK primary health care. Interventions Two informaticist projects to provide evidence based answers to questions arising in clinical practice and thereby support high quality clinical decision making by practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 16 publications
1
71
1
Order By: Relevance
“…Despite decades of experience, knowledge on the outcomes of DIS especially in primary care is scanty. Several studies proved that the number of medication errors in hospitals could be reduced by DIS [3]. In addition, studies showed considerable cost savings as a result of pharmacist-run DIS [4].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite decades of experience, knowledge on the outcomes of DIS especially in primary care is scanty. Several studies proved that the number of medication errors in hospitals could be reduced by DIS [3]. In addition, studies showed considerable cost savings as a result of pharmacist-run DIS [4].…”
Section: Introductionmentioning
confidence: 96%
“…Greenhalgh et al [3] suggested that an information service should be judged on at least two aspects of quality: an academic dimension, concerning the technical quality of the evidence based answers, and a service dimension, concerning the facilitation of questioning behaviour and implementation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Trisha Greenhalgh and colleagues [19] described and compared two models of 'informaticist' service, 'one more academically rigorous with a research component and little personal contact with practitioners and the other based in a general practice and one that took a more flexible, facilitative approach'.…”
Section: Introductionmentioning
confidence: 99%
“…Some libraries will experience demand for specialized services based on local needs. 56 Known solutions include variants of the clinical medical librarian role 57,58 or the medical informaticist role. 59 Library staff at a government research institute who provide researchers with assistance in the form of extensive literature searching and synthesis of gene annotation information indicated in unpublished interviews that they are both challenged and intellectually stimulated by the activity.…”
Section: Rolesmentioning
confidence: 99%